Urinary ascites in late onset of bladder injury post laparoscopic hysterectomy - Josette C. Dawkins; Gregory K. Lewis; Benjamin Christensen; Morris Wortman (Elsevier, 2017)
Urinary tract injuries are unfortunate complications of pelvic surgery. With the increasing popularity of minimally invasive surgery, a thorough understanding of electrosurgical instrumentation and their thermal spread is important to reduce patient injuries. The index patient was a 50 year old woman who underwent a supracervical hysterectomy 5 years prior to her presentation with pelvic pain and dysuria. When her symptoms failed to improve despite antibiotic and analgesic therapy, an abdominal CT scan revealed an ovarian cyst and ascites. A subsequent laparoscopy disclosed the presence of a bladder fistula and a diagnosis of urinary ascites was made. The patient then underwent a subsequent bladder fistula repair. Vesicoperitoneal fistulae (VPF) are rare and should be included in the differential diagnosis of the patient with acute onset ascites following gynecologic surgery. This case is the first case report of a VPF occurring 5 years following surgery.